Twentieth century writers, 1950-1990 - Verde, Thomas A. (Thomas Aquinas) 1958- (New York Facts on File, 1996)
This collection of short literary biographies of American writers of the second half of the twentieth century is the continuation of Twentieth Century Writers 1900-1950.
Keywords: Authors, American -- 20th century -- Biography -- Juvenile literature; Authors, American